NEW APPROACHES IN EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
As in every field, working with the reforms taking place in education requires studying the existing problems and trying to find solutions. From a pedagogical point of view, scientific approaches are also envisaged to be implemented within the framework of their work.